2014
DOI: 10.1186/1471-2288-14-26
|View full text |Cite
|
Sign up to set email alerts
|

A modified Wald interval for the area under the ROC curve (AUC) in diagnostic case-control studies

Abstract: BackgroundThe area under the receiver operating characteristic (ROC) curve, referred to as the AUC, is an appropriate measure for describing the overall accuracy of a diagnostic test or a biomarker in early phase trials without having to choose a threshold. There are many approaches for estimating the confidence interval for the AUC. However, all are relatively complicated to implement. Furthermore, many approaches perform poorly for large AUC values or small sample sizes.MethodsThe AUC is actually a probabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 27 publications
1
33
0
Order By: Relevance
“…ROC analysis is widely used in various fields, such as bioinformatics, medical statistics, radiology, pattern recognition, and machine learning [42-44]. In addition, some indicators from the ROC curve, such as the AUC, have been used as evaluation and construction of classifiers [45, 46]. Our results indicated that the AUC values of K trans were 0.790 and 0.816 at NRT and after the 5th RT, respectively.…”
Section: Discussionmentioning
confidence: 84%
“…ROC analysis is widely used in various fields, such as bioinformatics, medical statistics, radiology, pattern recognition, and machine learning [42-44]. In addition, some indicators from the ROC curve, such as the AUC, have been used as evaluation and construction of classifiers [45, 46]. Our results indicated that the AUC values of K trans were 0.790 and 0.816 at NRT and after the 5th RT, respectively.…”
Section: Discussionmentioning
confidence: 84%
“…Because the Wald interval depends on sample size, the method used for calculating the 95% CI of the AUC was a Wald model with correction for continuity. 7,8 The study unit for generating the AUC and 95% CI was the "patient." For that reason, we used the average of variables for each patient.…”
Section: Discussionmentioning
confidence: 99%
“…Cellular parameter values are expressed as means ± standard deviations (in μm); and, for ROC curve analysis, values are expressed as the area under the curve (AUC) with 95% confidence interval (CI). Because the Wald interval depends on sample size, the method used for calculating the 95% CI of the AUC was a Wald model with correction for continuity . The study unit for generating the AUC and 95% CI was the “patient.” For that reason, we used the average of variables for each patient.…”
Section: Methodsmentioning
confidence: 99%
“…Areas under receiver operating characteristic curves (AUCs) were computed for each finding with 95% confidence intervals computed by the exact Clopper-Pearson method. 25 In addition, we also estimated specificity and sensitivity that yield the highest harmonic mean with the 95% confidence intervals. We used the metrics module in the Python scikit-learn package version 0.18.2 (http://www.python.org) in the computation of the AUC and confusion matrix for sensitivity and specificity calculation.…”
Section: Evaluation Of the Algorithmsmentioning
confidence: 99%